2017
DOI: 10.1097/iae.0000000000001394
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Prone Positioning After Macular Hole Surgery Determined by Swept-Source Optical Coherence Tomography

Abstract: The SS-OCT protocol can significantly decrease the duration of the prone positioning without a reopening of the MH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…Some studies have monitored the timeline of macular hole closure by obtaining OCT imaging of the macula within days of vitrectomy surgery (through the gas-filled vitreous cavity) and used that information to curtail positioning. [113][114][115][116][117] In a recent meta-analysis of 251 cases by Hu et al concluded that no face down positioning was similar to face down positioning for holes smaller than 400µm, but face-down positioning may be beneficial for holes larger than 400µm. 118…”
Section: P189mentioning
confidence: 99%
“…Some studies have monitored the timeline of macular hole closure by obtaining OCT imaging of the macula within days of vitrectomy surgery (through the gas-filled vitreous cavity) and used that information to curtail positioning. [113][114][115][116][117] In a recent meta-analysis of 251 cases by Hu et al concluded that no face down positioning was similar to face down positioning for holes smaller than 400µm, but face-down positioning may be beneficial for holes larger than 400µm. 118…”
Section: P189mentioning
confidence: 99%
“…Moreover, the use of silicone oil or PFL as tamponades might not be mandatory in cases undergoing ART. Short-term tamponades like SF6 gas or air might be enough to achieve an adequate tamponade effect [10]. Inserting the graft tissue beneath the MH edges might be sufficient to secure the donor graft while integrating with the adjacent receptor macular tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for shortening FDP duration is supported by spectral-domain and swept-source OCT in the gas filled eye that shows MH closure as early as 0-2 days [27,28]. The reported rate of closure was 55-86% by POD1 [11,27,29].…”
Section: Current Trends In Positioningmentioning
confidence: 97%